2009
DOI: 10.1111/j.1439-0531.2009.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the μ Opioid Receptor and Effects of the Opioid Antagonist Naloxone on In Vitro Maturation of Oocytes Recovered from Anoestrous Bitches

Abstract: The mu-opioid receptor (MOR) is expressed in bovine, human, equine and canine oocytes, and in seasonal breeders, it is expressed with higher intensity during the anoestrous phase. Supplementation of in vitro maturation (IVM) medium with opioid agents, agonists or antagonists, was shown to affect oocyte maturation in several species such as rat, bovine and equine. This study reports the effects of supplementing IVM medium with naloxone (Nx), an opioid antagonist, on nuclear and cytoplasmic maturation rate of oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The mechanism of transmission is currently unknown but may include direct oocyte exposure to opioids. It is known that opioid receptors are expressed on oocytes and that stimulation delays oocyte maturation (Agirregoitia et al, 2012; Iorga et al, 2009), which can be reversed using the opioid antagonist naloxone (Dell’Aquila et al, 2002; Iorga et al, 2009). In fact, multiple studies have shown that endogenous opioids and their receptors play a substantial role in the development and function of the reproductive axis (Vuong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of transmission is currently unknown but may include direct oocyte exposure to opioids. It is known that opioid receptors are expressed on oocytes and that stimulation delays oocyte maturation (Agirregoitia et al, 2012; Iorga et al, 2009), which can be reversed using the opioid antagonist naloxone (Dell’Aquila et al, 2002; Iorga et al, 2009). In fact, multiple studies have shown that endogenous opioids and their receptors play a substantial role in the development and function of the reproductive axis (Vuong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that MOR is expressed in the bovine (91), human (92), canine (93) and equine (94) cumulus-oocyte complex (COC) (95). MOR, by inducing an increase in intracellular calcium, has been shown to participate in the cumulus-oocyte coupled signaling associated with oocyte maturation (94,95).…”
Section: Closing Remarksmentioning
confidence: 99%
“…Opioid receptors have been described in oocytes and granulosa cells from various species at the different maturation stages (Agirregoitia et al, ; Dang‐Nguyen et al, ; Dell'Aquila et al, ; Iorga et al, ; Lunger et al, ). In mammals, oocytes are arrested at germinal vesicle stage (GV) and during meiotic resumption they evolve to mature oocytes at metaphase II (MII).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried on to determine the function of opioid peptides during this event. The opioid antagonist naloxone appeared to modify the canine and porcine oocyte in vitro maturation, obtaining higher maturation rates when oocytes were matured in culture medium supplemented with low concentrations of naloxone (Dang‐Nguyen et al, ; Iorga et al, ). Besides, the addition of ß‐endorphin to the IVM culture resulted in an inhibition of the maturation rates in rats, bovine and equine oocytes (Dell'Aquila et al, ; Wai‐sum, ).…”
Section: Introductionmentioning
confidence: 99%